Effects of the inclusion of a mixed Psychrotrophic bacteria strain for sewage treatment in constructed wetland in winter seasons. Issue 4 (25th April 2018) - Tang, Meizhen; Li, Zhengtao; Yang, Yuewei; Chen, Junfeng; Jiang, Jie
Abstract : Constructed wetlands (CWs) have been used globally in wastewater treatment for years. CWs represent an efficient ecological system which is both energy-saving and low in investment for construction and operational cost. In addition, CWs also have the advantage of being easy to operate and maintain. However, the operation of CWs at northern latitudes (both mid and high) is sometimes quite demanding, due to the inhibitory effect of low temperatures that often occur in winter. To evaluate the wastewater treatment performance of a culture of mixed Psychrotrophic bacteria strains in an integrated vertical-flow CW, the removal rates of ammonia nitrogen (NH3 –N), chemical oxygen demand (COD), nitrite nitrogen ( NO 2 − − N ), nitrate nitrogen ( NO 3 − − N ) and total phosphorus (TP) were quantified at different bacterial dosages to determine the best bacterial dosage and establish kinetic degradation models of the mixed strains. The bacterial culture was made up of Psychrobacter TM-1, Sphingobacterium TM-2 and Pseudomonas TM-3, mixed together at a volume/volume ratio of 1 : 1 : 1 (at bacterial suspension concentrations of 4.4 × 10 9 ml −1 ). Results showed that the organic pollutants (nitrogen and phosphorus) in the sewage could be efficiently removed by the culture of mixed Psychrotrophic bacteria. The optimal dosage of this mixed bacteria strain was 2.5%, and the treatment efficiency of COD, NH3 –N, NO 2 − − N, NO 3 − − N, total nitrogen and TP were stable at 91.8%, 91.1%, 88.0%, 93.8%, 94.8% and 95.2%, respectively, which were 1.5, 2.0, 2.1, 1.5, 2.2 and 1.3 times those of the control group. In addition, a pseudo-first-order degradation model was a good fit for the degradation pattern observed for each of these pollutants.